Adoptive Natural Killer Cell Immunotherapy for Canine Osteosarcoma - Kisseberth, William C.; Lee, Dean A. (Frontiers in Veterinary Science, 2021)
Osteosarcoma is the most common primary bone tumor in both humans and dogs. It is a highly metastatic cancer and therapy has not improved significantly since the inclusion of adjuvant chemotherapy into disease treatment strategies. Osteosarcoma is an immunogenic tumor, and thus development of immunotherapies for its treatment, especially treatment of microscopic pulmonary metastases might improve outcomes. NK cells are lymphocytes of the innate immune system and can recognize a variety of stressed cells, including cancer cells, in the absence of major histocompatibility complex (MHC)-restricted receptor ligand interactions. NK cells have a role in controlling tumor progression and metastasis and are important mediators of different therapeutic interventions. The core hypothesis of adoptive natural killer (NK) cell therapy is there exists a natural defect in innate immunity (a combination of cancer‐induced reduction in NK cell numbers and immunosuppressive mechanisms resulting in suppressed function) that can be restored by adoptive transfer of NK cells. Here, we review the rationale for adoptive NK cell immunotherapy, NK cell biology, TGFβ and the immunosuppressive microenvironment in osteosarcoma, manufacturing of ex vivo expanded NK cells for the dog and provide perspective on the present and future clinical applications of adoptive NK cell immunotherapy in spontaneous osteosarcoma and other cancers in the dog.